2021
DOI: 10.3389/fmicb.2021.654494
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Regulation of Apoptosis by Flavivirus

Abstract: Apoptosis is a form of programmed cell death, which maintains cellular homeostasis by eliminating pathogen-infected cells. It contains three signaling pathways: death receptor pathway, mitochondria-mediated pathway, and endoplasmic reticulum pathway. Its importance in host defenses is highlighted by the observation that many viruses evade, hinder or destroy apoptosis, thereby weakening the host’s immune response. Flaviviruses such as Dengue virus, Japanese encephalitis virus, and West Nile virus utilize variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 165 publications
2
26
1
Order By: Relevance
“…This suggests that despite membrane permeabilization, the chromatin integrity is maintained, and, therefore, no empty space is visible within the Hoechst images of YFV plaques. Although YFV is typically considered as non-cytolytic [ 20 ], it was previously shown that different clones of YFV could induce small plaques or large plaques [ 21 ], probably reflecting different kinetics of cell death phases or a variable interaction with cell death mechanisms [ 26 ]. Indeed, it has been previously reported that YFV infection induces both pro-apoptotic [ 27 ] and anti-apoptotic [ 28 ] responses in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that despite membrane permeabilization, the chromatin integrity is maintained, and, therefore, no empty space is visible within the Hoechst images of YFV plaques. Although YFV is typically considered as non-cytolytic [ 20 ], it was previously shown that different clones of YFV could induce small plaques or large plaques [ 21 ], probably reflecting different kinetics of cell death phases or a variable interaction with cell death mechanisms [ 26 ]. Indeed, it has been previously reported that YFV infection induces both pro-apoptotic [ 27 ] and anti-apoptotic [ 28 ] responses in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Although YFV is typically considered as non-cytolytic [20], it was previously shown that different clones of YFV could induce small plaques or large plaques [21], probably reflecting different kinetics of cell death phases or a variable interaction with cell death mechanisms [26]. Indeed, it has been previously reported that YFV infection induces both pro-apoptotic [27] and anti-apoptotic [28] responses in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue virus is capable of having reciprocating effects on apoptosis regulation in cells ( Figure 5 ). All the four DENV serotypes potentially induce cellular apoptosis via the direct involvement of the cytotoxic M-proteins [ 97 ]. Cell-death-inducing proteins, such as RIPK2 and Daxx, are utilized during capsid-induced apoptosis [ 98 , 99 ].…”
Section: Dengue Virus Induced Cell Deathmentioning
confidence: 99%
“…The anti-apoptotic functions of DENV-2 are mediated by the inhibition of XBP-1 and increased Akt phosphorylation, so as to suppress the UPR stress response sequentially, in order to prohibit early apoptosis and extend the survival of the DENV by keeping the cell alive [ 111 , 112 ]. One of the other factors involved in apoptosis inhibition is the enrichment of calcium in the cell cytoplasm to protect the cell from apoptosis via mitochondrial damage [ 97 , 113 ].…”
Section: Dengue Virus Induced Cell Deathmentioning
confidence: 99%